2017
DOI: 10.3390/ijerph15010043
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Non-Fatal Health Outcomes in Pediatric General Trauma Studies

Abstract: When prevention efforts fail, injured children require high-quality health services to support their recovery. Disparities in non-fatal injury outcomes, an indicator of health-care quality, have received minimal attention. We evaluated the extent to which general trauma follow-up studies published in the peer-reviewed scientific literature provide evidence of socially patterned inequities in health, functional or disability outcomes ≥4 weeks after childhood injuries. Using a systematic search, we identified 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…Children from moderate and high SES areas had a higher HRQoL on average post-injury over time compared to children from low SES areas. This finding is consistent with systematic reviews of HRQoL and functional outcomes in children after injury [ 28 , 29 ]. There was a 12% higher relative risk over time of reporting no pain problems for children and adolescents from high SES areas compared to children and adolescents from low SES areas.…”
Section: Discussionsupporting
confidence: 91%
“…Children from moderate and high SES areas had a higher HRQoL on average post-injury over time compared to children from low SES areas. This finding is consistent with systematic reviews of HRQoL and functional outcomes in children after injury [ 28 , 29 ]. There was a 12% higher relative risk over time of reporting no pain problems for children and adolescents from high SES areas compared to children and adolescents from low SES areas.…”
Section: Discussionsupporting
confidence: 91%
“…There may even be scenarios that go in different directions—e.g., increases among social groups for some causes and decreases for others. Furthermore, a recent review of disparities in non-fatal injury outcomes found limited evidence of socially patterned inequities; the authors point to selection or retention biases being key limiting factors, as well as the focus on variations in outcomes only by sex [13]. These issues may explain the scarcity of studies on injury interventions identified in this review.…”
Section: Discussionmentioning
confidence: 97%
“…People from low socioeconomic status and from less affluent areas tend to die by injury to a greater extent than others [12]. Other reviews were target specific, by age group [13,14,15,16,17,18], injury cause, such as road traffic [19,20], falls [21], burns [22,23,24], or housing and neighbourhood conditions [25,26]. From among those reviews, only a few are specific to the European context, which is the focus of the present review, and to the best of our knowledge only one study [27] reviewed the literature on trends in social inequalities in injuries.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a large study, children between 1 and 4 years old accounted for the highest percentage of accidents in all ages (26.3%), sustaining mainly dentoalveolar injury to the primary dentition and soft tissue injuries. 2, 3,12 There is a need to identify whether most severe injuries are caused by a lack of supervision, especially when children come from lower economic groups. Moreover, the long-term outcome after severe injuries to the face, alveolar bone, and primary teeth is uncertain and unknown.…”
Section: Orofacial Tr Auma In Childrenmentioning
confidence: 99%
“…Moreover, the long-term outcome after severe injuries to the face, alveolar bone, and primary teeth is uncertain and unknown. 2, 3,12 There is a need to identify whether most severe injuries are caused by a lack of supervision, especially when children come from lower economic groups. 4…”
Section: Orofacial Tr Auma In Childrenmentioning
confidence: 99%